HLA-DR and DQB1 gene polymorphism in the North-western Colombian population (2002)
HLA?DRB1, DRB3, DRB4, DRB5 and DQB1 polymorphisms were studied using molecular methods in a population of 100 unrelated healthy individuals from an area in north?west Colombia (Medellin) inhabited by the “Paisa”, a community with features of a genetically isolated group. The most frequently observed specificities at the DRB1 locus were *07 (16.4%) and *15 (12%), and at the DQB1 locus *02 (18.8%) and *03 (33.6%), of which *0302 was the most prevalent allele (14.3%). The most polymorphic specificities were DRB1*04, 13 and 11, and DQB1*06. Both the HLA?DRB1 and DQB1 loci were in linkage disequilibrium. Haplotypes were estimated using maximum likelihood methods. The most frequent two locus haplotype was DRB1*07?DQB1*02 (6.6%) and these specificities were in linkage disequilibrium. Several unusual possible haplotypes were observed. Both the HLA?DRB1 and DQB1 locus were in Hardy–Weinberg equilibrium.